RRAD expression in gastric and colorectal cancer with peritoneal carcinomatosis - Kim, Hee Kyung (Sci Rep, 2019)
The role of Ras-related associated with diabetes (RRAD) in gastric cancer (GC) or colorectal cancer (CRC) has not been investigated. We aimed to investigate the biological and clinical roles of RRAD in GC and CRC and to assess RRAD as a therapeutic target. A total of 31 cancer cell lines (17 GC cell lines, 14 CRC cell lines), 59 patient-derived cells (PDCs from 48 GC patients and 11 CRC patients), and 84 matched pairs of primary cancer tissue and non-tumor tissue were used to evaluate the role of RRAD in vitro and in vivo. RRAD expression was frequently increased in GC and CRC cell lines, and siRNA/shRNA-mediated RRAD inhibition induced significant decline of tumor cell proliferation both in vitro and in vivo. A synergistic effect of RRAD inhibition was generated by combined treatment with chemotherapy. Notably, RRAD expression was markedly increased in PDCs, and RRAD inhibition suppressed PDC proliferation. RRAD inhibition also resulted in reduced cell invasion, decreased expression of EMT markers, and decreased angiogenesis and levels of associated proteins including VEGF and ANGP2. Our study suggests that RRAD could be a novel therapeutic target for treatment of GC and CRC, especially in patients with peritoneal seeding.